PERSIAPAN PELAKSANAAN MERDEKA BELAJAR DALAM KURIKULUM MERDEKA BELAJAR PADA SEKOLAH - Yusnadi Yusnadi (Sekolah Tinggi Agama Islam (STAI) Al-Wahliyah Barabai, 2022)
Freedom of learning can be used as an offer in the context of reconstructing the national education system. The national education system is being reconstructed to face the changing times and progress of the nation. The way to do this is to restore the essence of education, namely liberating education or using education to humanise humans. Teachers and students are subjects in the learning system under the concept of independent learning. This means that students do not only make the teacher a source of truth, but that in seeking the truth, the teacher and students collaborate. In the classroom, the teacher does not only standardise or instil the truth according to the teacher but also explores students' reasoning and critical thinking to find the truth. The momentum for learning independence is supported by the internet and technology that are growing. In addition, an education system that is not liberating or rigid can be changed. Administrative matters that are devoted to the workload of teachers and schools can be reformed. Thus, education units, teachers, and students can exercise freedom of learning, and be creative, innovative, and independent.